Comparative study on Well-to-Wheels emissions between fully electric and conventional automobiles in Istanbul. (October 2020) - Ozdemir, Abdulehad; Koc, Ilker Murat; Sumer, Bilsay
Highlights: Development of a driving cycle for Istanbul. Measurement of energy consumption and emissions by using generated driving cycle. Emission factor estimation of electricity production of Turkey. Comparison of emissions between electric and conventional passenger cars. Abstract: Transportation is one of the most significant sources of emissions across various industries. Projections indicate that electric vehicles (EVs) will attain a considerable portion of the vehicle market in the next decade. In this paper, Well-to-Wheels (WTW) greenhouse gas (GHG) emissions are analyzed both for conventional and EVs by using generated driving cycle. An up to date driving cycle for Istanbul is developed (so called Istanbul Driving Cycle) by using collected traffic data across various sections of the city. An internal combustion engine vehicle (ICEV) and an electric vehicle (EV) are tested on a chassis dynamometer under the same conditions to determine specific energy consumption and specific emissions. Turkey's electricity production infrastructure is analyzed and the emission factor of electricity production of Turkey is estimated. This paper concludes that, utilization of EVs instead of internal combustion engine vehicles (ICEVs) can save about 109.5 g CO2 equivalent (CO2eq ) per kilometer according to WTW methodology under the used Istanbul Driving Cycle. The WTW emissions of ICEV and EV are calculated as 183.4 g CO2eq /km and 73.9 g CO2eq /km respectively.